MODEL ON NATURAL SCIENCES SUBJECT (IPA) GRADE IV ELEMENTARY SCHOOL - Widiastuti, Shendi Kharisma (Universitas Pendidikan Ganesha, 2017)
This study aimed to produce a product namely learning media in the form of flashcardon the theme of